2022
DOI: 10.3390/ijerph19148729
|View full text |Cite
|
Sign up to set email alerts
|

Major Risk Factors for Mortality in Elderly and Non-Elderly Adult Patients Emergently Admitted for Blunt Chest Wall Trauma: Hospital Length of Stay as an Independent Predictor

Abstract: Background: Blunt thoracic trauma is responsible for 35% of trauma-related deaths in the United States and significantly contributes to morbidity and healthcare-related financial strain. The goal of this study was to evaluate factors influencing mortality in patients emergently admitted with the primary diagnosis of blunt chest wall trauma. Methods: Adults emergently admitted for blunt chest trauma were assessed using the National Inpatient Sample Database, 2004–2014. Data regarding demographics, comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Specifically, there was a 7.7% increase in the odds of mortality for each additional day spent in the hospital. Similarly, associations between mortality and HLOS were noted in multiple recent retrospective studies on patients emergently admitted with gastroparesis, hemorrhoids, duodenal ulcers, blunt chest wall trauma, tracheostomy, rectal malignancy, total hip arthroplasty, and paralytic ileus [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The HLOS was not a significant predictor for mortality in the elderly sample, despite elderly patients experiencing a longer HLOS ( Table 2 ).…”
Section: Discussionmentioning
confidence: 62%
“…Specifically, there was a 7.7% increase in the odds of mortality for each additional day spent in the hospital. Similarly, associations between mortality and HLOS were noted in multiple recent retrospective studies on patients emergently admitted with gastroparesis, hemorrhoids, duodenal ulcers, blunt chest wall trauma, tracheostomy, rectal malignancy, total hip arthroplasty, and paralytic ileus [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The HLOS was not a significant predictor for mortality in the elderly sample, despite elderly patients experiencing a longer HLOS ( Table 2 ).…”
Section: Discussionmentioning
confidence: 62%
“…Longer hospital length of stay has been shown to be detrimental in many diverse conditions [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 30 , 33 , 34 ]. Interestingly, for patients with ruptured abdominal aortic aneurysm, longer hospital length of stay was inversely correlated with mortality and thus improved outcomes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The database was created by AHRQ (the Agency for Healthcare Research and Quality), which has been frequently used nationally as a public data source for analysis of variegated types and qualities of patient care and their associated results. This has allowed us to perform a comprehensive and holistic path to research diseases, a path to the ideal way to treat and care for patients with those diseases, and ultimately a path to find how patients respond to both the diseases and treatments [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The NIS database includes certain weighting when constructing its sample of discharges and it excludes long-term acute care facilities and rehabilitation centers.…”
Section: Methodsmentioning
confidence: 99%
“…This can help explain our findings as HLOS can be used as a predictor for mortality in adult and elderly patients who did not undergo surgery for gastric ulcer. In fact, in the general literature, HLOS is associated with mortality in surgical patients admitted emergently due to other medical conditions, such as bleeding gastritis, blunt force trauma, tracheostomy, etc., whereas one study found a reverse relationship between HLOS and mortality for emergently admitted patients with ruptured abdominal aortic aneurysms [ 35 , 36 , 37 , 38 , 39 ]. A few recent retrospective cohort studies analyzed patients with phlebitis/thrombophlebitis, acute pancreatitis, C. difficile colitis, and colon cancer, which found a significant increase in odds of mortality after day 4, 6, 6, and 15 of admission, respectively [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors also found significant positive correlations between comorbidity and mortality [ 16 , 17 , 26 , 27 , 30 ]. In particular, some authors have specifically found respiratory diseases, liver disease and cardiac disease as important comorbidities affecting their respective medical conditions [ 38 , 44 ]. Our study found these same comorbidities to be significant as well.…”
Section: Discussionmentioning
confidence: 99%